Advances in the thin layer chromatographic analysis of counterfeit pharmaceutical products: 2008–2019. Issue 11 (21st July 2019) - Sherma, Joseph; Rabel, Fred
Abstract: Publications reporting thin layer chromatography (TLC) screening and high performance TLC (HPTLC)-densitometry quantification analyses of counterfeit pharmaceutical products are reviewed for the 2008–2019 period. Screening using TLC methods published in the Global Pharma Health Fund (GPHF) Minilab Manual and U.S. Food and Drug Administration (FDA) Compendium, as well as in other sources, are covered. Also included are publications on TLC analysis hyphenated with Raman and mass spectrometry; analyses of counterfeit traditional herbal medicines; earlier published reviews; transfer of screening methods for counterfeit pharmaceutical products in the Minilab Manual and FDA Compendium to HPTLC-densitometry using a model process; development of HPTLC-densitometry methods for pharmaceutical products not included in the Minilab Manual or FDA Compendium using the model process followed by development of corresponding Supplemental FDA Compendium TLC screening methods; and modified Minilab methods with simplified detection based on heating of silica gel F layers to produce fluorescence quenching zones (thermochemical activation) rather than detection using spray, dip, or vapor phase derivatization reagents. Some thoughts on future prospects for the field are also offered. Graphical Abstract: